Function of Vitellogenin receptor gene in reproductive regulation of Zeugodacus cucurbitae (Coquillett) after short-term high-temperature treatment - Yuyang Lian; Yuyang Lian; Sihua Peng; Sihua Peng; Jingjing Jia; Jinlei Li; Aqiang Wang; Shuyan Yang; Rongjiao Zheng; Xiaofeng Yang; Shihao Zhou; Shihao Zhou (Frontiers in Physiology, 2022)
Climate change has increased the frequency of extreme heat events. Zeugodacus cucurbitae (Coquillett) is an important tropical pest that typically changes its reproductive strategies in response to extremely high temperatures. Newly emerged adults of three consecutive generations (F1, F2, and F3) of Z. cucurbitae (Coquillett) were exposed to 25°C, 33°C, 37°C, 41°C, and 45°C treatments for 1 h to clarify the effects of short-term high temperatures on its reproduction. The influence of these temperatures on reproduction was evaluated using indicators, such as egg number. Newly emerged adults were exposed to 25°C and 45°C treatments for 1 h, and the expression of Vitellogenin receptor (VgR) gene in females was interfered with siRNA, and silencing efficiency of RNAi was evaluated. Results showed that short-term high temperatures, except for F1 treated at 45°C for 1 h to stimulate oviposition, exert a general adverse effect on the reproduction of Z. cucurbitae (Coquillett). All F3 died after the 45°C treatment for 1 h. Silencing of the VgR gene resulted in the significant downregulation of VgR gene expression at both 24 and 72 h. The egg number, oviposition days, and hatchability of eggs were significantly lower than those of other treatment groups after interference, and the inhibition effect of egg number was the most evident, with a decrease of 88.4% and 95.2% at 25°C and 45°C, respectively, compared with that of the Control Check (CK). Ovarian development speed and diameter were also significantly lower than those of other treatment groups after the interference. The results of this study can provide a theoretical reference for the integrated control of Z. cucurbitae (Coquillett) during high-temperature seasons.